Recent Advances in Biomechanics Research: Implications for Sports Performance and Injury Prevention - Luiz Vancini , Rodrigo; Andrade, Marília Santos; De Lira, Claudio Andre Barbosa; Russomano, Thais (Health Nexus, 2023)
This narrative review provides a comprehensive examination of the latest advancements in biomechanics and their implications for sports performance enhancement and injury prevention. Utilizing systematic literature search methodologies, the review draws on peer-reviewed articles, conference proceedings, and comprehensive review papers published between 2019 and 2023, sourced from databases such as PubMed, Google Scholar, and ScienceDirect. This article synthesizes findings from these sources to outline critical developments in the field of sports biomechanics. The review focuses on several key areas: technological innovations in biomechanics, biomechanical analysis of sports movements, injury prevention strategies, and the integration of biomechanical research into practical athletic training. Additionally, the review highlights the current challenges and limitations within the field and proposes future directions for research and application. By categorizing and analyzing recent literature into thematic areas, this review offers a detailed and structured overview of the state-of-the-art in sports biomechanics, emphasizing its significant impact on optimizing sports performance and reducing injury risks. The findings and discussions presented in this review are intended to inform researchers, practitioners, and athletes, contributing to the enhancement of sports science practices and athlete safety.